Les régimes d’avantages sociaux non-assurés (les RASNA) - Plamondon, Luc (Assurances, 1989)
Risks of loss can either be retained or transferred to an insurer. Voluntary risk retention in the area of life insurance or employee benefits compensation may be total or partial and requires administrative resources for adequate loss coverage. The author, Mr. Luc Plamondon, describes various self-insurance approaches in the field of employee benefits compensation plans. While some of these approaches call upon the voluntary action of the employer who provides the coverage, handling, financing and overall administration of claims, others may involve the insurer at different levels of management as well as different methods of insurance. Following is a summary of a speech given by the author last October to a group of Canadian lawyers.